Biophysical Modelling Approach For Beef Cattle Manure Management And Nutrients Flow Evaluation In Malaysian Feedlot Cattle - Tee, T. P.; Renly, A. (2011)
Biophysical models that estimate nutrients (e.g. nitrogen (N)) flow have been widely used for livestock manure management. They track the fate and pathway of nutrients through animal ration in feeding operation and identify the nutrient transformations process in the animal production system until field application. This type of model approach may be attempted for a single component or source of N losses (e.g. animal house, lagoon, compost, ammonia emission, leaching) (Muck et al., 1984; Burton and Beauchamp, 1986; Groot Koerkamp et al., 1998); or for entire animal production systems (N flows in farm-gate balances) integrated with cropping systems at farm level (Beauchamp, 1983; Oudendag and Luesink, 1998; Chambers et al., 1999; Hutching et al., 2001; Menzi et al., 2002). Though many of these nutrient balance models have been developed, most of them are for temperate climate in line with their animal farming system and conditions. However, it is clear that the different housing systems, manure handling methods (storage) and the biophysical processes (e.g. temperature and pH effects) affect the magnitude of nutrients losses. Therefore, the models from temperate countries may not be entirely adequate for Malaysian humid tropic conditions. Currently, no model exists that describes the whole nutrient cycle linking the flows from animal production phase (e.g. cattle feedlot) to waste handling phase (e.g. composting). There also no study or model on nutrient N flow processes for livestock manure management system prevalent in Malaysia. In view of this, biophysical models, namely the Beef Cattle Production and Manure Excretion (BCPME) Model will be developed. This model focuses on nutrients cycling at the whole farm-level from source (e.g. cattle feedlot production) to waste handling (composting phase) and investigates nutrient flows, associated losses and efficiency, and can thus be used for assessing the impact of animal manure on the surrounding environment.